Predicting corneal decompensation in Fuchs endothelial corneal dystrophy with Scheimpflug tomography and clinical parameters - Nilufer Yesilirmak; Vaël Souédan; Aurélie Pison; Jean Louis Bourges (Indian Journal of Ophthalmology)
Purpose: This study aims to evaluate the efficacy of various tomographic indices, both established and novel, in predicting endothelial decompensation leading to either spontaneous corneal transplantation or transplantation following cataract surgery in patients with Fuchs endothelial corneal dystrophy (FECD). Methods: In this cross-sectional, retrospective study, we reviewed the files of 93 eyes from 54 FECD patients undergoing regular follow-up. We recorded clinical metrics such as morning visual disturbance (MVD) and corrected distance visual acuity. In addition, we extracted topographic measurements including central corneal thickness (CCT); corneal volumes (CVs) within 3, 5, and 7 mm diameters (CV3, CV5, CV7); corneal central-to-peripheral volume ratios (CPVRs) for 3/5 mm (CPVR-3/5) and 3/7 mm (CPVR-3/7); peripheral volume index; thinnest point; corneal thickness spatial profile at 2, 4, 6, and 8 mm (CTSP2, CTSP4, CTSP6, CTSP8); corneal central-to-peripheral thickness ratio at 4 mm (CPTR4); and percentage of thickness increase at 2, 4, and 6 mm (PTI2, PTI4, PTI6), loss of regular isopachs (LRI), displacement of the thinnest point (DTP), and focal posterior surface depression (FPSD). Results: Receiver operating characteristic curves revealed a CCT area under the curve (AUC) of 0.732, with an optimal threshold of 596.5 µm yielding 79.7% sensitivity and 63.6% specificity. CTSP4 demonstrated an AUC of 0.706 with a 616.5-µm threshold (77.4% sensitivity, 60.6% specificity), and CPTR4 showed an AUC of 0.588 with a 0.963 threshold (62.3% sensitivity, 60.6% specificity). Notably, MVD presented a statistically significant odds ratio of 4.63 (95% confidence interval = 1.76–12.86). In univariate analyses, LRI, DTP, and FPSD were risk factors for progression, whereas in multivariate analyses, LRI was an independent risk factor for progression. Conclusion: The findings suggest that MVD and LRI serve as most significant predictive markers, while CCT, CTSP4, and CPTR4 were average predictive markers for FECD progression, underscoring their potential in guiding clinical decisions and interventions.